THE SPREAD OF THE CHOLERA EPIDEMIC IN TURKESTAN (American Journal of Research in Humanities and Social Sciences, 2022)
As we know, the Republic of Turkestan lived for a short time, but it had its place in the history of Uzbekistan. The difficult conditions in the republic, that is, the derailment of the economy due to political contradictions, the fact that social problems have become extremely acute, and the country has become the center of various epidemics, demanded special attention to health care. The Soviet government established the system based on its ideals. This process took place in Turkestan in a very complicated situation. Because the management in Turkestan was based on full military principles, the management and control of health care was initially entrusted to the military-sanitary department. The People's Commissar of Health, heads of regional health departments, regional doctors were appointed from the ranks of former military doctors in most cases. This created a number of difficulties in setting up the industry.